Pelatihan Internet of Things Dengan Database MySQL Untuk Meningkatkan Keterampilan Siswa Pada SMK Telkom Lampung - Selamet Samsugi; Debby Alita; Permata Permata; Riska Amalia Praptiwi; Feby Amanda; Lathifah Lathifah (Universitas Teknokrat Indonesia, 2023)
Telkom Lampung Vocational School has four competency skills that you can choose from. These four skill competencies are related to one another. The major related to the internet of things is TKJ, so this class was invited as a training participant. IoT training is indeed one of the requirements requested by Telkom Vocational School. This request is because the Internet of Things (IoT) is a technology that is being discussed lately. With this technology, every device that we use can later be connected to the internet. This training received good appreciation from the teacher and also the students who participated in this activity. The students were very enthusiastic in participating in the internet of things training because it added to their knowledge and skills. Hopefully the implementation of this training will add enthusiasm for students to continue learning and be able to continue to the higher education level.